The Impact of Systematic Laparoscopic Skills and Suture Training on Laparoscopic Hysterectomy Outcomes in a Brazilian Teaching Hospital - Anna Luiza Lobão Gonçalves; Helizabet Abdala Ayroza-Ribeiro; Raquel Ferreira Lima; Aline Estefane Eras Yonamine; Fabio Ohara; Paulo Augusto Galvão Ayroza-Ribeiro (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective To evaluate the impact of systematic laparoscopic skills and suture training (SLSST) on the total laparoscopic hysterectomy intra- and postoperative outcomes in a Brazilian teaching hospital. Methods A cross-sectional observational study in which 244 charts of total laparoscopic hysterectomy (TLH) patients operated from 2008 to 2014 were reviewed. Patient-specific (age, parity, previous cesarean sections, abdominal surgeries and endometriosis) and surgery-related variables (hospital stay, operative time, uterine volume and operative complications) were analyzed in three different time-frame groups: 2008-09 (I-1) - TLHs performed by senior attending physicians; 2010-11 (I-2) - TLHs performed by residents before the implementation of the SLSST program; and 2012-14 (I-3) - TLHs performed by residents after the implementation of the SLSST program. Results A total of 244 TLH patients (mean age: 45.93 years) were included: 24 (I-1), 55 (I-2), and 165 (I-3). The main indication for TLH was uterine myoma (66.4%). Group I-3 presented a decrease in surgical time compared to group I-2 (p=0.010). Hospital stay longer than 2 days decreased in group I-3 compared to group I-2 (p=0.010). Although we observed decreased uterine volume (154.2 cm3) in group I-2 compared to group I-1 (217.8 cm3) (p=0.030), logistic regression did not find any association between uterine volume and surgical time (p=0.103). Conclusion The total operative time for laparoscopic hysterectomy was significantly shorter in the group of patients (I-3) operated after the systematic laparoscopic skills and suture training was introduced in our hospital.